ANALISIS SELF-CONFIDENCE DALAM PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V SD KOTA BAUBAU - Nadila; Ayu Syukur; Anggi; Delia Dafista Zida; Nur Amalia Saleh; Annadwi Usman; Natsir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' self-confidence in solving mathematical problems remains one of the factors influencing mathematics learning outcomes in elementary schools. This study aimed to analyze the self-confidence of fifth-grade elementary school students in mathematical problem-solving in Baubau City. The study employed a quantitative approach using a descriptive quantitative research design. The population consisted of all fifth-grade students from public elementary schools in Baubau City, while the sample included 67 students selected from public elementary schools in Baubau City using purposive sampling. Data were collected through a self-confidence questionnaire and analyzed descriptively using frequencies and percentages. The average results across the participating public elementary schools showed that 66.52% of students were in the moderate category, 18.08% in the low category, and 15.40% in the high category. The findings indicate that students' self-confidence is predominantly at a moderate level. This suggests that most students have not yet developed optimal confidence in understanding, planning, implementing, and evaluating mathematical problem-solving. Therefore, teachers are encouraged to implement instructional strategies that enhance students' self-confidence through positive reinforcement, problem-based learning, group discussions, and opportunities for active participation in the learning process. Future research is recommended to involve a larger sample size and examine the relationship between self-confidence and mathematical problem-solving ability using correlational or experimental research designs.